Rancang Bangun Aplikasi Website Sekolah dan PPDB Online Madrasah Ibtidaiyah Darul Ghufron Menggunakan Metode Waterfall - Fuady, Syafrizal Arsyad; Pratiwi, Mariska Putri (Jurnal Nasional Ilmu Komputer, 2025)
The rapid development of technology has brought significant changes to the world of education, particularly in communication and information management. One example is Madrasah Ibtidaiyah Darul Ghufron, located in Batam, which has yet to utilize a website as a digital platform for managing academic and administrative information. Implementing a website in a school environment offers several benefits, including making information more accessible to the public, simplifying administrative processes such as new student registration, and reducing reliance on physical documents. The unavailability of a website causes the New Student Admission (PPDB) process to remain conventional, leading to delays in announcements and the risk of physical document damage or loss. This study aims to design and develop a school website with an online PPDB feature that can be accessed by prospective students, parents, and the general public. The website is designed using the waterfall system development method, which includes requirements analysis, design, implementation, testing, and maintenance stages. System testing is conducted through black box testing to ensure the website’s functionality meets user expectations. The study’s results indicate that this school website facilitates new student registration, provides broad access to school information, and assists teachers in managing applicant data, from registration to selection announcements. This website is expected to enhance efficiency and effectiveness in school data management and address the public's need for accessible information.